2004
DOI: 10.1007/s00424-004-1243-z
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomere-length dependence of lattice volume and radial mass transfer of myosin cross-bridges in rat papillary muscle

Abstract: We examined the sarcomere length-dependence of the spacing of the hexagonal lattice of the myofilaments and the mass transfer of myosin cross-bridges during contraction of right ventricular papillary muscle of the rat. The lattice spacing and mass transfer were measured by using X-ray diffraction, and the sarcomere length was monitored by laser diffraction at the same time. Although the lattice spacing and the sarcomere length were inversely related, their relationship was not exactly isovolumic. The cell volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 32 publications
7
31
0
Order By: Relevance
“…Recent experiments by Martyn et al (21) may lend some credence to this concept. These investigators demonstrated that an increase in either sarcomere length or externally applied osmotic pressure induces an increase in both the I 1,1 /I 1,0 intensity ratio and passive fiber stiffness, thus implicating an increase in the number of thin filament-associated cross-bridges under those conditions consistent with the aforementioned results of Yagi et al (37). Martyn et al (21), however, concluded that the observed changes in I 1,1 /I 1,0 intensity ratio were caused by changes in interfilament spacing.…”
Section: "Lattice Spacing Hypothesis" Revisitedsupporting
confidence: 69%
See 2 more Smart Citations
“…Recent experiments by Martyn et al (21) may lend some credence to this concept. These investigators demonstrated that an increase in either sarcomere length or externally applied osmotic pressure induces an increase in both the I 1,1 /I 1,0 intensity ratio and passive fiber stiffness, thus implicating an increase in the number of thin filament-associated cross-bridges under those conditions consistent with the aforementioned results of Yagi et al (37). Martyn et al (21), however, concluded that the observed changes in I 1,1 /I 1,0 intensity ratio were caused by changes in interfilament spacing.…”
Section: "Lattice Spacing Hypothesis" Revisitedsupporting
confidence: 69%
“…Moreover, we observed here that a small amount of myofilament lattice compression by application of 1% dextran (equivalent to 0.38 kPa applied osmotic compression) induced a change in the I 1,1 /I 1,0 intensity ratio from ϳ0.3 to ϳ0.45 in relaxed, isolated skinned myocardium. Various measurements of this parameter have been made previously in intact, nonskinned myocardium by Matsubara and colleagues (I 1,1 /I 1,0 ϭ 0.375) (23) and (I 1,1 /I 1,0 ϭ 0.581) (24), as well as Yagi and colleagues (I 1,1 /I 1,0 ϭ 0.4) (38) and (I 1,1 /I 1,0 ϭ 0.444) (37). Of interest, these values are similar to those observed in this present study in skinned rat cardiac trabeculae in the high-myofilament calcium sensitivity state, that is, those muscles that were compressed by application of Ͼ1.0% dextran (0.38 kPa).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The presence of the sarcolemma in intact striated fibers enables the cell to maintain an approximately constant volume as length changes, producing an inverse relationship between sarcomere length and interfilament lattice spacing (11,15,(41)(42)(43). In demembranated fibers, however, the permeabilized sarcolemma cannot maintain a constant volume, and lattice spacing is determined by a combination of sarcomere length, solution composition, and physical constraints, as well as attractive and repulsive forces between the filaments (11).…”
Section: Discussionmentioning
confidence: 99%
“…The number of such heads increased when the systolic tension was larger at higher heart rates, providing early evidence for the basis of the force-frequency relation. 66 Since then, isolated intact papillary muscle of rat and ferret, [67][68][69] rat trabeculae, 70 and mouse myocytes 71,72 also have been studied. The advantage of the isolated preparations is that the sarcomere length can be monitored with laser diffraction or video microscopy.…”
Section: Current and Past Saxs Studies From Myocytes To The In Situ Hmentioning
confidence: 99%